The Effect Of Online Learning On The Interest And Learning Outcomes Of Basic Chemistry Of Civil Engineering Students - Rizky Febriani Pohan; Muhammad Rahman Rambe (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Online learning is very effective and efficient during the current Covid-19 pandemic. Through this online learning, students can still carry out lectures without having to face to face with the lecturer. The purpose of this study was to determine the effect of online learning on the interest and learning outcomes of Basic Chemistry students of the Civil Engineering Study Program. The research samples were first semester students of the Civil Engineering Study Program, Graha Nusantara University, Padangsidimpuan, Academic Year 2020/2021 who took online learning during the Covid-19 pandemic, with a total of 40 respondents. The research method used to determine the effect of online learning on students' interest and learning outcomes was carried out using qualitative and quantitative research methods. Based on the Pearson Product Moment Correlation test, rcount> rtable or 4.401 > 0.2573 which means that H1 is accepted and Ho is rejected. So that online learning has an effect on interest in learning Basic Chemistry for first semester students of Civil Engineering Study Program, Graha Nusantara University, Padangsidimpuan, Academic Year 2020/2021. Based on the t-test conducted, it is found that tcount ≥ ttable is 6.22 ≥ 2.023, which means Ho is rejected or H1 is accepted. Thus, online learning also affects the learning outcomes of Basic Chemistry of first semester students of Civil Engineering Study Program, Graha Nusantara University, Padangsidimpuan, Academic Year 2020/2021.